Global warming - Bily, Cynthia A. (San Diego : Greenhaven Press, 2006)
A collection of essays exploring varying viewpoints on global warming, discussing such issues as its causes, its current effect on the environment, and the measures that need to be taken to combat it.
ch. 1. Is the threat of global warming real? -- 1. Global warming poses a serous threat / Geoffrey Lean -- 2. Global warming does not pose a serious threat / John F. McManus -- 3. Most scientists agree that global warming is a human-caused problem / Naomi Oreskes -- 4. Many scientists do not agree that global warming is a human-caused problem / Greening Earth Society -- ch. 2. What causes global warming? -- 1. Human activity causes global warming / Thomas R. Karl, Kevin E. Trenberth -- 2. Human activity does not cause global warming / William M. Gray -- 3. Sport utility vehicles contribute to global warming / Sierra Club -- 4. Sport utility vehicles do not contribute to global warming / Sal Rosken -- 5. Solar activity causes global warming / Ian Clark -- 6. Radiation from the earth's core causes global warming / Gary Novak -- ch. 3. What will be the effects of global warming? -- 1. Global warming is causing the polar ice caps to melt / Charles W. Petit -- 2. Natural fluctuations are causing the polar ice caps to melt / Jens Bischof -- 3. Global warming benefits life on earth / Dennis Avery -- 4. Global warming harms life on earth / Ross Gelbspan -- ch. 4. Should measures be taken to combat global warming? -- 1. Greenhouse gas emissions should be reduced / Fred Krupp -- 2. Greenhouse gas emissions need not be reduced / Sallie Baliunas -- 3. Greenhouse gas emissions cannot be reduced with current technology / William Kovacs -- 4. Nuclear power can combat global warming / John McCain -- 5. Nuclear power should not be used to combat global warming / Coalition of Groups -- 6. Alternative energy sources should be pursued / Lester R. Brown -- 7. Alternative energy should not be pursued / Jerry Taylor, Peter VanDoren -- 8. The Kyoto Protocol can help address global warming / Hamish McRae -- 9. The Kyoto Protocol cannot address global warming / Christopher DeMuth.
Includes bibliographical references (pages 191-202) and index.
Keywords: Global warming; Global warming; Global warming